Revitalization of a historical industrial port district - The goods station district in Antwerp - De Fossé, Marianne (International Planning History Society Proceedings, 2016)
Today the industrial heritage close to historic city centres is often part of major redevelopment projects. This is also the case for the former goods station district located in the north of Antwerp, close to the historic port of the city. The good station district was developed during the second half of the nineteenth century when new urban space became available after the demolition of the Spanish city walls in the 1860s. Henceforth, the city and its entrepreneurial citizens had the opportunity to develop a new industrial district with a goods station that linked the port with its hinterland. This industrial zone, which was highly productive during the second half of the nineteenth and the twentieth century, is characterized by many impressive warehouses. Recently however, this fascinating historic district started to undergo dramatic changes. The industry moved to the outskirts of the city and after a period of degeneration ambitious redevelopment plans were developed introducing new functions. The district is redeveloped as a residential district with offices. The vacant warehouses and factories attracted the attention of building promoters because of their valuable, large plots near the centre of the city. Some historic warehouses were demolished to make room for new office and apartment blocks, others were irreversibly changed. Although many warehouses still remain, their safeguarding is endangered by the speed and intensity by which the urban space is being redeveloped. It is, therefore, indispensable to rethink the value of the unique and diverse collection of remaining historical warehouses and their significance in the ever-changing fabric of the district. This paper aims to provide a scientific base to support the preservation and adaptive reuse of these warehouses, which still occupy large parts of the former goods station district. The paper analyses the planning history over the past 150 years of this particular district, located between the port and the goods station in Antwerp. Archival research (cadastral information, urban cartography and historic address books) allowed to define and to understand the establishment, functioning and evolution of the district. Additional research of building permits was necessary to define the historical importance of the warehouses, serving as a base to put forward criteria for their preservation. Furthermore, on-site investigations provided insight into the recent developments and were necessary to evaluate the reconversion projects of the warehouses and the changing integration of the latter in the urban fabric from a critical point of view. Finally, suggestions are formulated for respectful integration and renovation strategies. Henceforth, the study serves qualitative redevelopment projects as it is indeed essential to revalue historic industrial buildings in the evolving city centers and to investigate how this valuable heritage can be preserved for further generations.